Divorcio y su en la depresión en una mujer de 30 años de la Parroquia San Carlos - Leal Cepeda, Merilin Jacqueline (2023)
The present case study was based mainly on divorce, which is a separation process that two people go through who shared affective, emotional and coital ties, which affected the development of depression in a 30-year-old woman, bringing with her a series of signs symptoms at a physiological, cognitive, behavioral level preventing them from continuing their lives normally, to determine such a situation, various methodological techniques were implemented to obtain data, through clinical observation, semi-structured interview, clinical history and some tests psychometric tests, including the Beck Depression Inventory, the Zung Depression Self-Rate Scale (SDS) and the Rossemberg Self-Esteem Scale, allowing for a presumptive diagnosis based on manuals such as the DSM-V (300.04) Disorder persistent depressive disorder (dysthymia) and according to ICD-10 (F34.1) Dysthymia, for which psychological treatment was carried out using l Aaron Beck's Cognitive-Behavioral Therapy, which consisted of applying various therapeutic techniques such as psychoeducation, differentiating facts, thoughts and feelings, explaining how thoughts create feelings, reasons to die and reasons to live, activity programming and 4-stroke breathing to improve the patient's condition.